Effect of boron element on photoaging in rats - Gul, Seda; Cicek, Demet; Şahin, Kazım; Ozercan, Ibrahim Hanifi; Orhan, Cemal; Demir, Betul; Er, Besir (Elsevier Science Sa, 2022)
Background: The present study further assessed the effects of oral and topical applications of boron, which is known to have antiinflammatory and wound healing effects, on photoaging. Methods: A total of 49 eight-week-old female Wistar albino rats randomly divided into seven groups (control, shaved control, shaved+UVB, topical dermabor 2% (D2), and %5 (D5), systemic sodium perborate tetrahydrate (SPT) 2% (SPT2) and 4% (SPT4). To induce an experimental photoaging, the rats were exposed to UVB at an emission spectrum of 290-320 nm. Biochemical, molecular, skin, histological, and collagen content analyzes were made at the end of the study. Results: Increased skin inflammatory parameters (COX-2, IL-8, NF-KB, IL-6, and TNF-alpha) levels in UVB-exposed groups were inhibited in all treatment groups. The tissue level of hydroxyproline and elastase was found to decrease in all UVB-exposed group. The level of hydroxyproline was significantly higher in the D2 and D5 groups than in the SPT2 and SPT4 groups. The level of elastase was significantly lower in the D2 and D5 groups than in the SPT2 and SPT4 groups. Conclusions: In future, boron may be developed as a functionally protective treatment against photoaging caused by UVB, and may be included in sun protection systems.
Keywords: Boron; Photoaging